2013
DOI: 10.4081/or.2013.e11
|View full text |Cite
|
Sign up to set email alerts
|

Using a reconstruction locking compression plate as external fixator in infected open clavicle fracture

Abstract: Open clavicle fracture is an uncommon injury mostly caused by severe direct trauma. It is often associated with multiple organ injuries. Generally, surgical intervention with debridement and fracture repair is always indicated in order to prevent infection, non-union, and malalignment. In situations of bony exposure and significant contamination concomitant with severe soft tissue damage, the external fixation is the treatment of choice because of the possibility it offers of providing stable fixation with min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
(9 reference statements)
0
9
0
1
Order By: Relevance
“…External fixators used in present clinical practice have various limitations, including insufficient fixation stiffness and strength, leading to poor healing, or high construct profiles, resulting in nonpatient friendly physical burden [13][14][15][16][17]. It is therefore essential to design a novel prototype of an external fixator for tibial fracture to increase rigidity and strength while reducing the profile of the fixation constructs.…”
Section: Introductionmentioning
confidence: 99%
“…External fixators used in present clinical practice have various limitations, including insufficient fixation stiffness and strength, leading to poor healing, or high construct profiles, resulting in nonpatient friendly physical burden [13][14][15][16][17]. It is therefore essential to design a novel prototype of an external fixator for tibial fracture to increase rigidity and strength while reducing the profile of the fixation constructs.…”
Section: Introductionmentioning
confidence: 99%
“…The use of external fixation for the treatment of clavicle fractures has previously been described 2–5 8 9. Schuind et al 3 described a case series of clavicle external fixators, employed for a variety of different indications.…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been referred to as ‘supercutaneous plating’. It has been suggested that this method may offer a number of advantages over conventional external fixation methods 8 9. The locking screw head mechanism provides an additional degree of stability to the construct, particular in its resistance of angular forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…External fixators used in present clinical practice are linked to various limitations, including insufficient fixation stiffness and strength, leading to poor healing, or high profile of the constructs, resulting in non-patient friendly physical burden [13][14][15][16][17]. It is therefore essential to design a novel prototype of an external fixator for tibial fracture to increase the rigidity and strength, while reducing the profile of the fixation constructs.…”
Section: Introductionmentioning
confidence: 99%